The political economy of media in reporting the individual Candidate Bagyo Wahyono-FX Suparjo in the 2020 Surakarta City Election - Heri Budianto; Afdal Makkuraga Putra; St. Arief Setiadji (Penerbit Universiti Kebangsaan Malaysia, 2023)
The 2020 Surakarta City Regional Head Election was in the spotlight of Indonesian newspapers Solopos and Radar Solo ashe attraction of election is the presence of independent candidates, Bagyo Wahyono-FX Suparjo, who are competitors to the Gibran Rakabuming Raka-Teguh Prakosa pairing who were promoted to become a political party. With the difference in political caste between the two candidates, this study aims to dissect the practice of messages presented by two local newspapers in Surakarta, Solopos and Radar Solo towards the independent candidates. This study deployed Norman Fairclough's critical analysis method with approaches and paradigms of Vincent Mosco's political economy media theory. The results concluded Radar Solo tended to favor Gibran Rakabuming Raka in terms of choices and sentences presented to the audience. Meanwhile, Solopos chose a more neutral stance for both candidates. Messages presented by Solopos and Radar Solo need to provide a balanced space for the Bagyo Wahyono-FX Suparjo pairing. Various factors, such as the lack of optimal use of the Bagyo Wahyono-FX Suparjo pairing of media as a means of campaigning and the lack of a personal campaign agenda, influence this balance. Another significant finding is that there is a design and a more significant political interest behind one's appearance, which makes the dynamics of the Surakarta City Election run in vain.